Dispersal and Transmission of Avian Paramyxovirus Serotype 4 among Wild Birds and Domestic Poultry - Yin, Renfu; Zhang, Pingze; Liu, Xinxin; Chen, Yanyu; Tao, Zhi; Ai, Lili; Li, Junjiao; Yang, Yingying; Li, Mingxin; Xue, Cong; Qian, Jing; Wang, Xueli; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Avian paramyxovirus serotype 4 (APMV-4) is found sporadically in wild birds worldwide, and it is an economically important poultry pathogen. Despite the existence of several published strains, very little is known about the distribution, host species, and transmission of APMV-4 strains. To better understand the relationships among these factors, we conducted an APMV-4 surveillance of wild birds and domestic poultry in six provinces of China suspected of being intercontinental flyways and sites of interspecies transmission. APMV-4 surveillance was conducted in 9,160 wild birds representing seven species, and 1,461 domestic poultry in live bird markets (LMBs) from December 2013 to June 2016. The rate of APMV-4 isolation was 0.10% (11/10,621), and viruses were isolated from swan geese, bean geese, cormorants, mallards, and chickens. Sequencing and phylogenetic analyses of the 11 isolated viruses indicated that all the isolates belonging to genotype I were epidemiologically connected with wild bird-origin viruses from the Ukraine and Italy. Moreover, chicken-origin APMV-4 strains isolated from the LBMs were highly similar to wild bird-origin viruses from nearby lakes with free-living wild birds. In additional, a hemagglutination-negative APMV-4 virus was identified. These findings, together with recent APMV-4 studies, suggest potential virus interspecies transmission between wild birds and domestic poultry, and reveal possible epidemiological intercontinental connections between APMV-4 transmission by wild birds.